ABC Information, Fairness Perceptions, and Interfirm Negotiations - Masschelein, Stijn; Cardinaels, Eddy; Van den Abbeele, Alexandra (The Accounting Review, 2012)
ABSTRACT We examine the effect of more precise cost information on contract renegotiations between supply-chain parties. Specifically, we experimentally investigate the benefits of activity-based costing (ABC) information to address common supply-chain inefficiencies that are caused by the buyer or the seller, but have the same underlying costs. Results suggest that the impact of more precise cost information depends crucially on the cause of the inefficiency that parties need to address during the negotiation. ABC information increases the total joint profit in the supply chain. However, ABC information increases the seller's perceptions of the fairness of the buyer's arguments for contract changes only when the buyer causes the inefficiency but not when the seller causes the inefficiency. The combined effect of ABC information on joint profit and fairness perceptions thus increases the buyer's profit only when buyer causes the inefficiency but not when the seller causes the inefficiency. Data Availability: Data are available from the first author upon request.